Synergistic Effect of Thrombomodulin Promoter -33G/A Polymorphism and Smoking on the Onset of Acute Myocardial Infarction - Li, Yi-Heng; Chen, Jyh-Hong; Tsai, Wei-Chuan; Chao, Ting-Hsing; Guo, How-Ran; Tsai, Liang-Miin; Wu, Hua-Lin; Shi, Guey-Yueh (Thrombosis and Haemostasis, 2002)
Thrombomodulin is an endothelial cell surface receptor for thrombin. It plays an important role in the regulation of blood coagulation by decreasing thrombin activity and activating protein C. This study examined the possible association between the thrombomodulin -33G/A polymorphism and acute myocardial infarction. We recruited 278 patients (mean age 57.5 years, 241 men) with documented myocardial infarction and 450 age-and sex-matched control subjects. Polymerase chain reaction and single-strand conformation polymorphism was used to define the thrombomodulin -33G/A polymorphism. The frequency of the thrombomodulin GA+AA genotype among patients with myocardial infarction was higher than that in control subjects (22.7% vs. 16.2%, odds ratio [OR] 1.5, 95% confidence interval [CI] 1.0 to 2.2). The -33G/A polymorphism (GA+AA genotype) was significantly associated with myocardial infarction (OR 1.6, 95% CI 1.1 to 2.5) as was hypertension, diabetes mellitus and smoking. Among young myocardial infarction patients (age ≤45 years, n = 72), the frequency of -33G/A polymorphism was more significantly higher than that in control subjects (29.2% vs. 16.2%, OR 2.1, 95% CI 1.2 to 3.8). The -33G/A polymorphism (OR 2.3, 95% CI 1.3 to 4.1) and smoking (OR 4.5, 95% CI 2.5 to 7.9) were the only independent risk factors for young myocardial infarction. Furthermore, among patients who did not smoke, the polymorphism was associated with a nonsignificant increase in the risk of young myocardial infarction (OR 1.9, 95% CI 0.6 to 5.6); whereas, in the presence of smoking, the increase was statistically significant (OR 2.3, 95% CI 1.2 to 4.7). Smoking carriers of the thrombomodulin -33G/A polymorphism had a nearly 10-fold increased risk of young myocardial infarction (OR 9.8, 95% CI 4.3 to 22.4) when compared with nonsmoking non-carriers. We concluded that there was a significant association between the thrombomodulin -33G/A polymorphism and myocardial infarction in our population, especially in young patients. The clinical effect of this genetic factor was enhanced by smoking.
Keywords: Myocardial infarction; polymorphism; smoking